STUDY ON FAST NUCLEAR REACTOR WITH HIGH MOBILITY, HIGH WORKING TEMPERATURE, AND HELIUM COOLANT - Imada Samosir, Andrew
Advances in world’s industry and technology causes exponential rise in energy demand, and therefore requires a solution. Problems arose from nuclear power plants at the moment are the tendency of nuclear reactors to be massive in scale, its operation and construction which are complicated at best, the need for large capital investment, and its limited application. The solution is to create Fast Nuclear Reactor working at high pressure – high temperature Brayton Gas Cycle for optimal thermal efficiency in addition to greater utility potential, with a small size that enables it to be transported by various transportation mode such as railway train, using lightweight materials to achieve lower reactor mass, and finally inherently designed to be modular. Using SRAC, we simulate the Fast Modular Reactor with gas coolant to test the feasibility of the solution. Results show that it is feasible to create a reactor with more than 10 year operating time before easy online refuelling, with output energy above 200 MW thermal, with reactor size that fits inside a typical railway carriage, and total reactor mass under 300 ton.